The Types of Politeness Strategies Used at Perama Tour and Travel: Pragmatics Study - Walio, Yowel; Laba, I Nenggah; Kamayana, I Gusti Nyoman (LPPM Universitas Dhyana Pura, 2024)
Politeness is a form of one's conscious action when speaking to others. This study aims to analyse the conversational politeness used at Perama Tour and Travel. This type of research is qualitative research with language politeness methods and causal factors used at Perama Tours and Travels. The data in this study obtained from incoming and outgoing emails and various conversations at Perama Tour and Travel. The results of this study indicate that visitors and Perama Tour staff send and receive information to each other to travel through Perama Tour and Travel. Factors causing impoliteness include namely, the way of speaking before starting the next conversation, but at first there was a misunderstanding in conveying information that, feeling uncomfortable in the service because of an error in conveying information. In this research, there are two problems analysed, namely, what types of politeness strategies used at Perama Tours and Travel? What factors of politeness used at Perama Tours and Travel? In this research, it analyses based on language politeness and also impoliteness in serving Perama Tour customers. The presence of polite language towards customers will create a sense of comfort for the interlocutor. Likewise, when the politeness factor, the language used is not in accordance with the wishes of the visitor, discomfort often occurs in the service. This research focuses on language politeness towards Perama Tour and Travel Customers. Efforts to increase politeness are to provide examples directly to visitors by giving appreciation to customers using good and polite language or attitude.